Factors Influencing Non-Timber Forest Products on Household Welfare in Maraba Sector, Huye District, Rwanda - Mizero, Alexis; Ndayisaba, Felicien; Nduwamungu, Jean; Agbolosoo, John Atsu (Jurnal Manajemen Hutan Tropika, 2025)
Non-timber forest products (NTFPs) enhance rural household income. In Rwanda, natural forests cover 11.9% of the land and are key for biodiversity conservation, providing water catchment protection, tourism, medicinal plants, honey, and handicraft materials. Despite the forest sector's economic potential, rural residents dependent on NTFPs face challenges, leading to high unemployment and poverty. This research examines how socio-economic factors affect Huye district NTFP collectors' welfare. Using multi-stage sampling, 152 participants were selected, and data was collected through structured questionnaires in 2022. Data analysis used SPSS version 29 and STATA version 16 for multiple linear regression. The research identified NTFPs including fruits, vegetables, honey, traditional medicine, mushrooms, building materials, bush meats, art crafts, fuel, forage, and fodder. The main reasons for NTFP participation included food provision, income generation, education and health expenses, obtaining forage and fodder, building materials, and traditional medicine. Factors like distance to forest, training, extension services, credits, and market information significantly influenced household income. The study recommends increasing forestland allocation for NTFPs and implementing agroforestry systems to boost household income. Reforestation and afforestation initiatives should enhance forest conservation and biodiversity. The Ministry of Lands and Forestry and stakeholders should establish payment systems for ecological services benefiting community residents